2019
DOI: 10.1111/hex.12887
|View full text |Cite
|
Sign up to set email alerts
|

Assessing community readiness for early intervention programmes to promote social and emotional health in children

Abstract: Objective Evidence for early intervention and prevention‐based approaches for improving social and emotional health in young children is robust. However, rates of participation in programmes are low. We explored the dynamics which affect levels of community readiness to address the issues of social and emotional health for pregnant women, young children (0‐4 years) and their mothers. Setting A deprived inner‐city housing estate in the north of England. The estate falls within the catchment area of a project th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…The authors reported that the number of interviews per community varied between one and 33 (mean = 7.3, SD = 5.9, median = 6, six studies provided no information on the number of interviews per community), with 15% of studies using less than the recommended four interviews per community. This is in line with studies published since 2013 that followed the recommendations of the CR handbook and conducted an average of four to eight interviews per community (e.g., in [15][16][17][18][19]). However, Kesten et al.…”
Section: Discussionsupporting
confidence: 88%
“…The authors reported that the number of interviews per community varied between one and 33 (mean = 7.3, SD = 5.9, median = 6, six studies provided no information on the number of interviews per community), with 15% of studies using less than the recommended four interviews per community. This is in line with studies published since 2013 that followed the recommendations of the CR handbook and conducted an average of four to eight interviews per community (e.g., in [15][16][17][18][19]). However, Kesten et al.…”
Section: Discussionsupporting
confidence: 88%
“…The authors reported that the number of interviews per community varied between one and 33 (mean = 7.3, SD = 5.9, median = 6, six studies provided no information on the number of interviews per community), with 15% of studies using less than the recommended four interviews per community. This is in line with studies published since 2013 that followed the recommendations of the CR handbook and conducted an average of four to eight interviews per community (e.g., in [ 15 19 ]). However, Kesten et al [ 20 ] used the concept of theoretical saturation (i.e., no new concepts are expected by conducting more interviews) to determine the necessary number of interviews for assessing CR for overweight and obesity prevention in pre-adolescent girls.…”
Section: Discussionsupporting
confidence: 87%
“…From the previous calculation, the community readiness score was 10.3. Referring to the table above, the level of readiness of the Ngargogondo Village community in the tourism aspect of the Language Village is in the preparation stage (fifth position), which means that the leader plays an active role in designing planning seriously, with the simple support of the village community (Edwards et al, 2000;Plested et al, 2006;McElroy et al, 2011;Paltzer et al, 2013;Tri-Ethnic Center, 2014;Islam et al, 2019). Re-highlighting the leadership dimensions of the Language Village"s tourism aspect, the score was found to be 10.6.…”
Section: Level Of Community Readiness In Establishing a Global Village Tourism Sectormentioning
confidence: 99%
“…Based on the interval score of 0.4, the level of community readiness in the global village aspect can be seen in Table 8. Referring to the table above and the community readiness score of 8.9, the level of readiness of the Ngargogondo Village community in the global village aspect is in the preplanning stage (fourth position), which means that the community is aware and acknowledges that there is an issue or problem being faced, must take some preventive efforts or countermeasures, but these efforts have not been focused in detail (Edwards et al, 2000;Plested et al, 2006;McElroy et al, 2011;Paltzer et al, 2013;Tri-Ethnic Center, 2014;Islam et al, 2019). Each dimension"s score in the global village aspect tends to be smaller than the Language Village aspect"s score.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation